Gc subtyping in Malaysians and in Indonesians from North Sumatra - Tan, Soon Guan; Gan, Yik Yuen; Kudus, Asuan; Abdullah, Faridah (Springer-Verlag, 1981)
Malays, Chinese and Indians from peninsular Malaysia; Ibans and Bidayuh from Sarawak state, Northern Borneo; and Bataks, Minangkabau and Javanese from North Sumatra, Indonesia, were subtyped for Gc (group-specific component) by polyacrylamide gel isoelectric focusing. All eight populations investigated were found to be polymorphic for three common alleles, GcIF, GclS and Gc2